2017
DOI: 10.1111/ahg.12180
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive candidate gene analysis for symptomatic or asymptomatic outcomes of Leishmania infantum infection in Brazil

Abstract: Summary Genetic risk factors contribute to asymptomatic versus symptomatic visceral leishmaniasis (VL) outcomes following infection with Leishmania infantum. We therefore carried out a family-based (N=918 post-quality control fully genotyped and phenotyped individuals) candidate gene study for symptomatic VL or asymptomatic delayed type hypersensitivity (DTH) skin test phenotypes in highly endemic neighborhoods of northeast Brazil. A total of 248 SNPs were genotyped in 42 genes selected as candidates on the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
2
7
0
3
Order By: Relevance
“…For example, a population genetics study provided evidence for the link between TGF beta pathway and progression of L . infantum infection [36]. Recently it was shown that clinical severity of VL is associated with changes in the profile of IgG Fc N-Glycopepetide and that this is restored after treatment [37].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a population genetics study provided evidence for the link between TGF beta pathway and progression of L . infantum infection [36]. Recently it was shown that clinical severity of VL is associated with changes in the profile of IgG Fc N-Glycopepetide and that this is restored after treatment [37].…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis of the association amongst three genotypes (GA, AA, and GG) of TGFBR2 rs6785358 and the pathological type of hypospadias revealed statistical differences in the frequencies of GA or AA genotype, but not in the GG genotype, between the case and control groups. TGFBR2 rs6785358 polymorphism was reported to be correlated to the visceral leishmaniasis phenotype [ 27 ], which meant that TGFBR2 rs6785358 polymorphism was associated with the development of disease. The results of the present study also revealed that patients carrying a G allele of TGFBR2 rs6785358 might exhibit an increased risk of hypospadias.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to IL-10, other cytokines might facilitate Leishmania persistence in macrophages. Several studies with L. tropica -, L. infantum - or L. donovani -infected mice and with humans from Leishmania -endemic areas suggested a pathogenic role for TGF- β [16] , [221] , [222] , [223] , a known suppressor of macrophage functions and Th1 differentiation [93] , [224] , [225] . For type I IFNs (IFN- α/β ) , at least five different categories of mechanisms of action have been described that could support parasite survival in vivo .…”
Section: Macrophages As Niche For Long-term Parasite Persistencementioning
confidence: 99%